2019
DOI: 10.2147/idr.s204199
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quinolone resistance mechanisms among third-generation cephalosporin resistant isolates of <em>Enterobacter</em> spp. in a Bulgarian university hospital</p>

Abstract: Background: There have been no reports in Bulgaria about quinolone resistance determinants among Enterobacter spp. Aims: To investigate plasmid and chromosomal quinolone resistance rates among 175 third-generation cephalosporin resistant Enterobacter spp. isolates (167 Enterobacter cloacae complex and eight Enterobacter aerogenes isolates) collected at a university hospital in Varna, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
6
2
1
Order By: Relevance
“…Moreover, the ESBLs gene bla TEM was popular in this study, which was totally different from the predominant bla CTX-M-15 in Bulgaria. 40 We found that the carrying rates of ESBLs were higher in carbapenemresistant ECC than in carbapenem-sensitive ECC, compared with other reports. 41 The production of ESBLs or the overexpression of AmpC combined with disrupted membrane permeability (outer membrane protein decreased or loss) was another reason for carbapenem resistance.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Moreover, the ESBLs gene bla TEM was popular in this study, which was totally different from the predominant bla CTX-M-15 in Bulgaria. 40 We found that the carrying rates of ESBLs were higher in carbapenemresistant ECC than in carbapenem-sensitive ECC, compared with other reports. 41 The production of ESBLs or the overexpression of AmpC combined with disrupted membrane permeability (outer membrane protein decreased or loss) was another reason for carbapenem resistance.…”
Section: Discussioncontrasting
confidence: 51%
“…Moreover, the ESBLs gene bla TEM was popular in this study, which was totally different from the predominant bla CTX-M-15 in Bulgaria. 40 We found that the carrying rates of ESBLs were higher in carbapenem-resistant ECC than in carbapenem-sensitive ECC, compared with other reports. 41 …”
Section: Discussioncontrasting
confidence: 51%
“…This genus produces acetic and propionic acids using fermentable fibers as their substrate (35). Infections of the urinary tract, lower respiratory tract, bloodstream, and damage to soft tissues are caused by Enterobacter (36). Therefore, in this experiment, FA supplementation increased the abundance of beneficial bacteria and reduced the abundance of harmful bacteria in the gut.…”
Section: Discussionmentioning
confidence: 87%
“…Given the location of the qnr gene in plasmids containing many resistant genes, including beta-lactamases, the higher frequency of quinolone-resistant isolates in ESBL-producing E. cloacae strains in the present study might be reasonable. Markovska et al reported a PMQR gene frequency of 59% in Enterobacter strains [ 27 ]. In Azargon et al's study, similar to the results of the present study, the highest PMQR gene frequencies were found in ESBL-producing isolates.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Bolourchi et al's study, 3 of 4 isolates of E. cloacae carried this gene [ 29 ]. Markovska et al reported the frequency of qnrB as 90% [ 27 ]. Among 113 strains of E. cloacae , the frequency of qnrS was determined to be 17.7%.…”
Section: Discussionmentioning
confidence: 99%